ROCK DISCONTINUITY PATTERNS DEVELOPMENT ALONG CRUSHED ZONES SEPARATED BY FAULT MOVEMENT - Hendarmawan -; Hirnawan, F. -; Muslim, D. - (Bionatura, 2011)
Multivariate analysis was applied to rock-discontinuities taken from areas, in which folded and faulted sedimentary rocks occur. The purpose of the analysis is to verify the responses of these discontinuities to faults, from which the really existing fault can be delineated and mechanism and intensity of the deformation on Tertiary sediments underlying Quaternary sediments can be revealed that explain the intensity of neotectonism as the deformation continued on the Quaternary deposits. The sample parameters consist of strike and dip of both bedding planes and left also right diagonal joint sets respectively. From every site of two study areas two sample groups were taken from two rock-blocks separated by a fault. The analyses on the six parameters of the samples exhibit the contribution of each parameter to the rejection of the hypotheses of no effect of fault can be examined, which lead into a conclusion about how far does the parameter indicate the existing fault. The conclusion in Study Area 1 is that both right and left joint sets are significantly affected by reverse fault, suggesting that these two joint sets in uplifted rock-block were still affected by the folding process after reverse movement of the fault. Then, in Study Area 2, means of strike of bedding planes and right joint set significantly differ as a result of left lateral-slip fault certainly moving along a fractured zone.Key words: Discontinuity responses to fault, mechanism of deformation, intensity of deformation, neotectonism